The Role of Microalgae in Enhancing Anaerobic Digestion: A Bibliometric Review - İremsu Kayan; Nilgün Ayman Oz (Aquatic Sciences and Engineering)
Anaerobic digestion (AD) is a well-established and extensively explored technology for waste management. However, the literature review related to the effect of microalgae on biogas production in the anaerobic co-digestion with different substrates is limited. Using scientometric tools can offer valuable insights into research gaps and emerging trends, facilitate the updating of scientific datasets, and expand knowledge in this field. Therefore, this bibliometric review will focus on the investigation of the advancements, trends, and recent updates in the co-digestion of microalgae with different substrates. The Web of Science database was used for document selection, and the bibliometric analysis was conducted using the VOSviewer version 1.6.19 software. The findings of this study reveal that, up until 2024, the major focus areas in the field are environmental studies related to biogas production, emphasizing microbiological and engineering aspects. Key opportunities and trends identified include the integration of feedstock pretreatment before AD to enhance biogas yield and quality. Adding microalgae as a co-substrate in anaerobic reactors has emerged as a promising strategy to boost AD process efficiency. Microalgae contribute additional organic matter and nutrients for AD and provide environmental benefits such as carbon sequestration and wastewater treatment, aligning with Sustainable Development Goals (SDGs). Gaining a deeper understanding of the role of microalgae in the systems is essential to establishing AD as a profitable and sustainable waste management solution, offering substantial economic and environmental advantages.